Performance study of Hybrid Wireless Mesh Protocol(HWMP) for IEEE 802.11s WLAN Mesh Networks - Bari, S.M. Sadakatul; Anwar, Farhat; Masud, M. H. (2012)
Wireless Mesh Network (WMN) have been envisioned as an important solution to the next generation wireless networking which can be used in wireless community networks, wireless enterprise networks, transportation systems, home networking and last-mile wireless internet access. Many proprietary mesh solutions were developed by individual vendor but in order to interoperability; IEEE forms a task group called IEEE 802.11s to develop an integrated mesh networking solution. Hybrid Wireless Mesh protocol (HWMP) and airtime metrics as default routing protocol and routing metrics set by the task group. There is few test bed and many simulation studies have been done to evaluate the performance of the HWMP protocol with the assumption of unique type of flow with fixed packet size and packet rate. However, real networks carry a diverse application (video, voice, FTP, Email etc) with different characteristics (packet size, data rate). In this paper, we are investigated and analyzed the performance of HWMP protocol under such heterogeneous application characteristics.